PRESSURE RELATIONSHIP WHEN ASSOCIATING WITH TEETH WITH SENSITIVE DENTAL IN COMMUNITY, KANDANG VILLAGE, KECAMATAN DARUL IMARAH ACEH BESAR DISTRICT - Andriani Andriani; Elfi Zahara (Poltekkes Kemenkes Jambi, 2019)
Background: Sensitive teeth occur because there is thinning in the enamel layer so that the dentin layer below becomes exposed. This study aims to find out the relationship of toothbrushing pressure with the occurrence of sensitive teeth in Kandang Village, Kecamatan Darul Imrah, District of Aceh Besar in 2018. Methods: This study was analytical with a cross sectional approach. The population in this study were all communities in Kandang Village, a sample of 89 people taken based on simple random techniques. Data were obtained by interviewing using a questionnaire. Results: The results showed that of the 89 cage villagers who used pressure when brushing their teeth there were 60.7% sensitive teeth (p = 0.026). Conclusion: It can be concluded that there is a relationship between pressure when brushing teeth with sensitive teeth (p <0.05). and recommended to all people who experience sensitive teeth to be able to maintain and maintain the health of their teeth and mouth.